Application of Genetic Research Techniques in Myopia Research - Shi, Chongwei (International Journal of Computer Science and Information Technology, 2024)
The rapid development of genetic research techniques has provided new perspectives and tools for the study of myopia. This paper reviews several key genetic technologies, including genome sequencing, gene editing technologies, genetic association studies, and epigenetic technologies, and explores their applications in myopia research. Through genome sequencing, researchers can identify genetic variations associated with myopia; gene editing technologies offer powerful tools to explore gene functions and their impact on myopia; genetic association studies help reveal genes and genetic markers related to myopia; and epigenetic technologies provide insights into how environmental factors influence the genetic mechanisms underlying myopia. Despite significant achievements, current research faces challenges such as data complexity, ethical issues, and technical limitations. Future advancements in technology and research are expected to continue expanding the application of genetic techniques in myopia research, offering new strategies and methods for the prevention and treatment of myopia.